Two-year Test–Retest Reliability in High School Athletes Using the Four- and Two-Factor ImPACT Composite Structures: The Effects of Learning Disorders and Headache/Migraine Treatment History. (1st July 2017) - Brett, Benjamin L; Solomon, Gary S; Hill, Jennifer; Schatz, Philip
Abstract: Objective: This study examined the test–retest reliability of the four- and two-factor structures (i.e., Memory and Speed) of ImPACT over a 2-year interval across multiple groups with premorbid conditions, including those with a history of special education or learning disorders (LD; n = 114), treatment history for headache/migraine ( n = 81), and a control group ( n = 792). Methods: Nine hundred and eighty seven high school athletes completed baseline testing using online ImPACT across a 2-year interval. Paired-samples t -tests documented improvement from initial to follow-up assessments. Test stability was examined using Regression-based measures (RBM) and Reliable change indices (RCI). Reliability was examined using intraclass correlation coefficients (ICC). Results: Significant improvement on all four composites were observed for the control group over a 2-year interval; whereas significant differences were observed only on Visual Motor Speed for the LD and headache/migraine treatment history groups. ICCs ranges were similar across groups and greater or comparable reliability was observed for the two-factor structure on Memory (0.67–0.73) and Speed (0.76–0.78) composites. RCIs and RBMs demonstrated stability for the four- and two-factor structures, with few cases falling outside the range of expected change within a healthy sample at the 90% and 95% CIs. Conclusion: Typical practices of obtaining new baselines every 2 years in the high school population can be applied to athletes with a history of special education or LD and headache/migraine treatment. The two-factor structure has potential to increase test–retest reliability. Further research regarding clinical utility is needed.